2017
DOI: 10.3390/biomedicines5020030
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Cell Death Pathways for Inducible Cell Elimination to Modulate Graft-versus-Host-Disease

Abstract: Hematopoietic stem cell transplantation is a potent form of immunotherapy, potentially life-saving for many malignant hematologic diseases. However, donor lymphocytes infused with the graft while exerting a graft versus malignancy effect can also cause potentially fatal graft versus host disease (GVHD). Our group has previously validated the inducible caspase-9 suicide gene in the haploidentical stem cell transplant setting, which proved successful in reversing signs and symptoms of GVHD within hours, using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…Second, NK-92 cells can spontaneously kill tumors by recognizing diverse ligands via a variety of NK activating receptors. Among these, the NKG2D receptor is one of the major signaling pathways involved in cancer immunosurveillance [41][42][43][44]. As we demonstrated that CAR-and NKG2D-dependent activation pathways do not reciprocally interfere, it is conceivable that they can act in concert in engineered NK-92 cells to potentiate tumor destruction.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Second, NK-92 cells can spontaneously kill tumors by recognizing diverse ligands via a variety of NK activating receptors. Among these, the NKG2D receptor is one of the major signaling pathways involved in cancer immunosurveillance [41][42][43][44]. As we demonstrated that CAR-and NKG2D-dependent activation pathways do not reciprocally interfere, it is conceivable that they can act in concert in engineered NK-92 cells to potentiate tumor destruction.…”
Section: Discussionmentioning
confidence: 72%
“…Hence, repeated infusions of irradiated NK-92 cells are required as a means to circumvent their limited survival, but the approach has drawbacks in terms of costs and patient compliance. In this regard, introducing a suicide gene into NK-92/CAR cells might represent a valid safety option alternative to irradiation, because it would likely allow a single administration of effectors that are subsequently amenable to being completely switched off after exerting their therapeutic activity or in the case of severe, unwanted toxicity [42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, repeated doses of CID were able to eliminate a residual percentage of repopulating cells that express low levels of iC9 [ 144 ], indicating that repeated doses of CID to activate inducible genes are safe and functional. Other dimerizer systems take advantage of Fas [ 145 ] or other molecules in the apoptosis or necroptosis pathways, as reviewed elsewhere [ 146 ]. Lastly, expression of a cell surface antigen on engineered T cells such as truncated CD20 or EGFR allows the elimination of T cells with FDA-approved mAbs that induce complement activation and/or antibody-dependent cellular cytotoxicity (ADCC) [ 147 , 148 ].…”
Section: Preventing Toxicity Of Car T Cellsmentioning
confidence: 99%
“…Its immunogenicity could preclude persistence and activity of the infused therapeutic cells. In the setting of donor lymphocyte infusion post allogeneic HSCT this still resulted in anti-tumor effect, likely due to the slow kinetic of cell's elimination (15). The requirement for ganciclovir may limit its use in patients with cytomegalovirus infection where this agent is a primary treatment option.…”
Section: Introductionmentioning
confidence: 99%
“…The DiC9 suicide gene is a chimeric protein composed of a drug-binding domain linked in frame with a component of the apoptotic pathway, allowing conditional dimerization and apoptosis of the transduced cells after administration of a nontherapeutic small molecule dimerizer, such as AP1903 or BB homodimerizer (15)(16)(17)(18)(19). Straathof et al (19) and Tey et al (20) validated the DiC9 construct for T cell applications, demonstrating optimal transduction efficiency, expansion, and elimination of DiC9 T cells with strong expression of the transgene (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%